Method for improving anaerobic corrosion hydrogen evolution effect of nanoscale zero-valent iron
The polymer wraps nano zero-valent iron to form a protective layer, which solves the problem of low hydrogen evolution efficiency under mild conditions, and achieves efficient and environmentally friendly hydrogen production.
Patent Information
- Application Number
- CN202311249675.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-03-25
AI Technical Summary
The existing nano zero-valent iron has low hydrogen evolution efficiency under mild conditions, and commonly used acidic or alkaline solutions are highly corrosive, which will corrode the reaction equipment.
The polymer is wrapped in situ with nano zero-valent iron, forming a macromolecular protective layer, inhibiting the formation of a passivation layer, and improving the corrosion and hydrogen evolution performance of nano zero-valent iron.
The corrosion and hydrogen analysis efficiency of nano zero-valent iron in aqueous solution is improved, the corrosion of nano zero-valent iron is slowed down, the secondary pollution of the environment is avoided, and the accumulated hydrogen production is improved.
Smart Images

Figure CN119683566A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for improving the anaerobic corrosion hydrogen evolution effect of nano zero-valent iron, belonging to the technical field of corrosion hydrogen evolution. Background Art
[0002] Hydrogen is considered a green energy source due to its high calorific value, cleanliness and abundant sources, and is the best alternative energy source to replace traditional fossil fuels. However, as a secondary energy source, hydrogen must be produced from other energy sources. At present, most hydrogen production methods are based on fossil fuels, such as steam reforming of natural gas. However, there are constraints such as low conversion rate, high cost and environmental pollution, which limit its application. In addition, the utilization of hydrogen energy is largely limited by safe and efficient hydrogen storage. Therefore, it is increasingly important to develop new methods for compact and convenient hydrogen sources.
[0003] In an anaerobic environment, zero-valent iron is prone to corrosion and hydrogen evolution reaction in water, that is, the electrons of iron first migrate to water molecules, generating hydrogen atoms adsorbed on the surface of iron, and the two hydrogen atoms further combine to generate hydrogen. The reaction process can be described as follows:
[0004] Fe+2H2O→Fe 2+ +2OH - +H2↑
[0005] Studies have shown that nano zero-valent iron has a better hydrogen evolution effect due to its small particle size and large specific surface area. However, under mild conditions, the reaction between nano zero-valent iron and water is limited. This may be because the passivation layer (metal oxide or hydroxide) formed on the metal surface prevents the contact between the metal and water, and the hydrogen production reaction is blocked. The reaction of nano zero-valent iron with acidic or alkaline solutions to generate hydrogen can avoid the influence of the passivation layer, but these reagents are highly corrosive and will corrode the reaction equipment. Therefore, in order to achieve high hydrogen production, it is imperative to modify the nano zero-valent iron to a certain extent. Summary of the invention
[0006] In order to solve the problem of low hydrogen evolution efficiency of existing nano zero-valent iron, the present invention provides a method for improving the hydrogen evolution efficiency of nano zero-valent iron in aqueous solution, which is simple to operate, highly efficient and avoids secondary pollution to the environment. Nano zero-valent iron is in-situ encapsulated by a polymer, and a macromolecular protective layer is physically covered on the surface of the nano zero-valent iron, so that the particles remain in a dispersed state while inhibiting the formation of a passivation layer, thereby improving the corrosion hydrogen evolution performance of the nano zero-valent iron. The coated nano zero-valent iron can slow down the corrosion of the nano zero-valent iron while maintaining the high activity of the nano zero-valent iron in the inner core.
[0007] In view of the above purpose, the present invention first provides a method for improving the anaerobic corrosion hydrogen evolution effect of nano zero-valent iron, comprising the following steps:
[0008] (1) adding a polymer precursor solution into a reaction device, and introducing nitrogen gas to maintain an anaerobic environment in the reaction device;
[0009] (2) uniformly dispersing the nano-zero-valent iron into the polymer precursor solution in step (1) to obtain a mixed solution, stirring the mixed solution under anaerobic conditions to obtain a nano-zero-valent iron composite material, and collecting the generated hydrogen using a gas collection bag;
[0010] Wherein, the polymer precursor includes any one of sodium carboxymethyl cellulose, extracellular polymer and sodium dodecyl sulfate.
[0011] In one embodiment of the present invention, when the polymer precursor is sodium carboxymethyl cellulose, the concentration of the polymer precursor solution is 0.2-1.0 g / L; when the polymer precursor is extracellular polymer or sodium dodecyl sulfate, the concentration of the polymer precursor solution is 6-14 mg / L.
[0012] In one embodiment of the present invention, in the mixed solution, the concentration of the nano zero-valent iron is 10 g / L.
[0013] In one embodiment of the present invention, when the polymer precursor is sodium carboxymethyl cellulose, the concentration of the polymer precursor solution is 0.2-1.0 g / L, preferably 0.4 g / L.
[0014] In one embodiment of the present invention, when the polymer precursor is an extracellular polymer, the concentration of the polymer precursor solution is 6-14 mg / L, preferably 10 mg / L.
[0015] In one embodiment of the present invention, when the polymer precursor is sodium dodecyl sulfate, the concentration of the polymer precursor solution is 6-14 mg / L, preferably 12 mg / L.
[0016] In one embodiment of the present invention, step (1) further includes adjusting the pH of the polymer precursor solution to 7±0.2. After adjusting the pH of the polymer precursor solution, the air in the system is blown out by introducing nitrogen to avoid interference from pH and air.
[0017] In one embodiment of the present invention, in step (2), the stirring includes mechanical stirring, the stirring speed is 200-400 rpm, and the stirring time is 30 minutes, so that the polymer is wrapped on the surface of the nano zero-valent iron to form a nano zero-valent iron composite material. The polymer is wrapped on the surface of the nano zero-valent iron in the form of microparticles, thereby forming a sustained-release protective layer.
[0018] The present invention also provides a nano zero-valent iron composite material prepared by the method.
[0019] The present invention also provides an application of the nano zero-valent iron composite material in the field of corrosion hydrogen evolution.
[0020] Beneficial effects of the present invention:
[0021] (1) The present invention improves the corrosion hydrogen evolution effect of nano zero-valent iron by adding polymer precursors such as CMC, EPS, and SDS and modifying nano zero-valent iron in an anaerobic environment. This is mainly because CMC, EPS, SDS and other polymers are coated on the surface of nano zero-valent iron, and the electrostatic repulsion of nano zero-valent iron is enhanced, thereby reducing the agglomeration and passivation of nano zero-valent iron, thereby enhancing the corrosion hydrogen evolution ability of nano zero-valent iron.
[0022] (2) When the addition amounts of CMC, EPS and SDS were 400 mg / L, 10 mg / L and 12 mg / L respectively, these polymers could not only form a protective layer on the surface of nano zero-valent iron, but also enhance the hydrogen evolution effect of nano zero-valent iron. The cumulative hydrogen production of nano zero-valent iron modified by these polymers within 14 days was 1042 mL, 1066 mL and 1210 mL respectively, which was 6.11% to 10.30% higher than that of the blank group. The characterization results showed that the coating material formed a protective layer on the surface of nano zero-valent iron, enhancing its hydrogen evolution performance. Through the characterization of the materials before and after the reaction, it can be found that the iron core gradually transformed into iron oxide during the corrosion and hydrogen evolution of the nano zero-valent iron composite material, and the coated material had better hydrogen production effect and longer reaction time than nano zero-valent iron.
[0023] (3) The material of the present invention is simple to synthesize. In an aqueous solution system, the optimal concentration of the coating material is determined. By improving the stability of the nano zero-valent iron and thus increasing the amount of hydrogen production, the preparation and application of a corrosion-resistant nano zero-valent iron composite material are achieved. The present invention has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram of the reaction device of the present invention and a schematic diagram of the principle of hydrogen evolution by corrosion;
[0025] Figure 2 The corrosion and hydrogen evolution of nano zero-valent iron with different concentrations in aqueous solution;
[0026] Figure 3 The hydrogen evolution of nano-zero-valent iron composite materials formed after modification with polymer precursors of different concentrations in aqueous solution; (a) sodium carboxymethyl cellulose; (b) extracellular polymers; (c) sodium dodecyl sulfate;
[0027] Figure 4 TEM images of nano-zero-valent iron and nano-zero-valent iron composites;
[0028] Figure 5 XRD images of nano-zero-valent iron and nano-zero-valent iron composites.
[0029] Figure 6 FTIR images of nano-zero-valent iron and nano-zero-valent iron composites. Specific implementation method:
[0030] Example 1
[0031] A method for improving the anaerobic corrosion hydrogen evolution effect of nano zero-valent iron comprises the following steps:
[0032] (1) Prepare 400 mL of 0.4 g / L sodium carboxymethyl cellulose (CMC) solution in a reaction bottle, adjust the pH of the solution to 7±0.2, and pass nitrogen gas for 5 min to maintain an anaerobic environment in the reaction device;
[0033] (2) Evenly dispersing the nano-zero-valent iron into the sodium carboxymethyl cellulose solution in step (1) to obtain a nano-zero-valent iron dispersion, wherein the concentration of the nano-zero-valent iron in the dispersion is 10 g / L, mechanically stirring the dispersion under anaerobic conditions to obtain a nano-zero-valent iron composite material, and collecting the generated hydrogen with a gas collecting bag, wherein the stirring speed is 200-400 rpm and the stirring time is 30 min.
[0034] The reaction device of this method is as follows Figure 1 As shown in (a), Figure 1 (b) is a schematic diagram of the reaction. The water displacement method was used to test the hydrogen production. The test showed that the cumulative amount of hydrogen produced by this method within 14 days was 1042 mL.
[0035] Embodiment 2:
[0036] The difference between Example 2 and Example 1 is that the concentration of sodium carboxymethyl cellulose is changed, and its concentration is set to 0.2 g / L, 0.4 g / L, 0.6 g / L, 0.8 g / L, and 1.0 g / L, respectively.
[0037] Embodiment 3:
[0038] The difference between Example 3 and Example 1 is that sodium carboxymethyl cellulose is replaced with extracellular polymer (EPS), and the concentrations thereof are set to 6 mg / L, 8 mg / L, 10 mg / L, 12 mg / L, and 14 mg / L, respectively.
[0039] Embodiment 4:
[0040] The difference between Example 4 and Example 1 is that sodium carboxymethyl cellulose is replaced by sodium dodecyl sulfate (SDS), and its concentration is set to 6 mg / L, 8 mg / L, 10 mg / L, 12 mg / L, and 14 mg / L, respectively.
[0041] Comparative Example 1 Hydrogen evolution of nanometer zero-valent iron in pure water system
[0042] 400 mL of aqueous solution was added to the reaction bottle and purged with nitrogen for 5 minutes to maintain an anaerobic environment. In a nitrogen environment, the nano-zero-valent iron was evenly dispersed in the aqueous solution. The amount of hydrogen evolution was determined by the drainage method and the hydrogen was collected with a gas collection bag to determine the optimal nano-zero-valent iron concentration for corrosion hydrogen evolution. Among them, the concentrations of nano-zero-valent iron in the solution were set to 6 g / L, 8 g / L, 10 g / L, 12 g / L, and 14 g / L, respectively.
[0043] Result analysis:
[0044] (1) Hydrogen evolution of different concentrations of nano-zero-valent iron in pure water system
[0045] The hydrogen evolution of nano-zero-valent iron with different concentrations in pure water system is shown in Figure 2. Figure 2 As shown. According to the reaction equation, the production of hydrogen depends on the concentration of nano zero-valent iron. However, due to the characteristics of the condensed state and the passivated state, the amount of hydrogen evolution is lower than the theoretical value. Therefore, the optimal gas production concentration of nano zero-valent iron needs to be determined based on the actual amount of hydrogen evolution. Regardless of the concentration of nano zero-valent iron, the gas production rate is fast and the gas production can reach about 65% of the total gas volume in the first two days of the reaction, indicating that the hydrogen evolution of nano zero-valent iron is a fast process. In addition, nano zero-valent iron is a highly reducible and active substance. It is easy to generate precipitation on the surface of nano zero-valent iron during the reaction with water. This surface deactivation will reduce the recovery efficiency of H2, resulting in a significant decrease in the H2 yield after three days of reaction. Compared with the theoretical prediction, the H2 recovery rate generated by nano zero-valent iron corrosion is between 40% and 60%. These results show that the amount of hydrogen evolution of nano zero-valent iron increases with the increase of nano zero-valent iron concentration, but when it exceeds a certain concentration, the amount of hydrogen evolution is greatly reduced due to the agglomeration and surface passivation of nano zero-valent iron. The gas production of five different concentrations of nano zero-valent iron in the reaction stage were 69.33 mL / g, 83.86 mL / g, 109.1 mL / g, 81.5 mL / g, and 76.43 mL / g, respectively. Taking into account the economic benefits and microbial tolerance, and combined with the actual amount of hydrogen evolution, in this reaction system, nano zero-valent iron at 10 g / L is conducive to the corrosion hydrogen evolution.
[0046] (2) Hydrogen evolution of nano-zero-valent iron composites synthesized with different concentrations of coating materials in pure water system
[0047] The hydrogen evolution of nano-zero-valent iron composites synthesized by coating materials with different concentrations in pure water system is shown in Figure 2. Figure 3 As shown. Figure 3 (a) It can be seen that when sodium carboxymethyl cellulose is used to coat nano zero-valent iron, the hydrogen production rate decreases significantly with the increase of sodium carboxymethyl cellulose concentration, but the cumulative gas production shows a trend of first decreasing, then increasing, and finally decreasing. When the CMC concentration is 400 mg / L, the final cumulative H2 amount in 14 days reaches 1042 mL. The cumulative H2 amount of the uncoated nano zero-valent iron is increased by 6.11%. Figure 3 (b) It can be seen that when EPS is used to coat nano zero-valent iron, as the EPS concentration increases to 12 mg / L, the hydrogen production rate does not show a significant decrease, but the cumulative gas production shows a trend of first decreasing, then increasing, and finally decreasing. When the EPS concentration is 12 mg / L, the final cumulative H2 amount in 14 days reaches 1066 mL. This is 8.55% higher than the cumulative H2 amount of uncoated nano zero-valent iron. Figure 3 (c) It can be seen that when SDS is used to coat nano zero-valent iron, as the SDS concentration increases to 12 mg / L, the hydrogen production rate does not show a significant decrease, but the cumulative gas production shows a trend of first decreasing, then increasing, and finally decreasing. When the SDS concentration is 12 mg / L, the final cumulative H2 amount in 14 days reaches 1210 mL. The cumulative H2 amount of the uncoated nano zero-valent iron is increased by 10.30%.
[0048] Compared with uncoated nano-zero-valent iron, at a suitable polymer precursor concentration, the composite material can not only improve the hydrogen evolution performance, but also extend the hydrogen evolution reaction time to 14 days. At a stable nano-zero-valent iron dose, the increase in hydrogen production may be attributed to more available reaction sites. CMC uses the electrostatic adsorption of carboxylic acid groups, the bidentate bridge formed between the carboxyl group and the oxidized shell of the nanoparticles, and the hydrogen bond to make the nano-zero-valent iron have better dispersibility and stability. EPS forms a stable Fe-EPS complex on the surface of nano-zero-valent iron, which can inhibit the formation of passivation products. The corrosion of iron induced by anaerobic microorganisms further proves that EPS secreted by microorganisms can promote the corrosion of iron. SDS is a foaming agent that can increase the gaps between particles. Coated nano-zero-valent iron can weaken the agglomeration effect of nanoparticles, improve the stability of nanoparticles in the environment, and to a certain extent reduce the toxicity of nano-zero-valent iron to microorganisms. These coating materials improve the reactivity of nano-zero-valent iron and enhance its active sites, thereby improving the hydrogen evolution capacity while weakening particle aggregation. The experimental results show that the nano-zero-valent iron composites formed by encapsulating 0.4g / L CMC, 10mg / L EPS and 12mg / L SDS can enhance the hydrogen evolution performance. These nano-zero-valent iron composites are denoted as CMC 400 -nZVI 10 、EPS 10 -nZVI10 、SDS 12 -nZVI 10 .
[0049] (3) TEM image of nano-zero-valent iron composite material
[0050] CMC 400 -nZVI 10 、EPS 10 -nZVI 10 、SDS 12 -nZVI 10 The characterization images of these three nano zero-valent iron composite materials are shown in Figure 2. Figure 4 TEM image ( Figure 4 (a) shows the morphology of uncoated nano-ZVI nanoparticles. Uncoated nano-ZVI nanoparticles are generally spherical with smooth surface. Nano-ZVI nanoparticles are connected into chain structures through magnetic dipole interaction and aggregation. In contrast, nano-ZVI nanoparticles are covered by flocculation precipitation after reaction with water ( Figure 4 (A)). Iron diffuses outward from the nano-ZV Fe core as Fe 0 The disappearance of the core and the appearance of the hollow oxide shell inhibit the corrosion and hydrogen evolution of nano-zero-valent iron. The coated nanoparticles have a shell-like coated Fe due to the steric hindrance effect of the surface coating. 0 Compared with bare nano-zero-valent iron, the surface coating material has better dispersibility and lower aggregation tendency. According to the transmission electron microscopy image, the coated nanoparticles also have an independent spherical structure, in which Fe 0 is enclosed in an oxide shell, such as Figure 4 (b), 4(c) and 4(d). After 14 days of aging, these nano-ZVI composites began to lose their spherical shape in oxygen-free water and began to form needle-like plates, as shown in Figure 4 (B), 4(C) and 4(D). The loss of the iron core and the appearance of the hollow oxide shell prove that under anaerobic water conditions, iron ions diffuse outward from the nano-zero-valent iron core and form a new oxide phase on the particle surface. Compared with nano-zero-valent iron that has not been aged in anaerobic water, in anaerobic water, nano-zero-valent iron and composite particles are gradually corroded by water and a passivation layer is formed on the particle surface. Figure 5 The nano-zero-valent iron and CMC before aging in oxygen-free water (fresh) and after aging are shown respectively. 400 -nZVI 10 、EPS 10 -nZVI 10 、SDS 12 -nZVI 10 The XRD pattern of Figure 5It can be seen that the peak of iron ions in the aged sample becomes weaker, and the peak intensity of magnetite and (or) hematite increases.
[0051] (4) FTIR image of coating material
[0052] Infrared spectrum of nano-zero-valent iron ( Figure 6 Compared with (a), the binding energy of aged nano-zero-valent iron oxide is larger, indicating that the aged nano-zero-valent iron reacts with water to form iron oxide covering the surface of the particles, which is consistent with the XRD results. Figure 6 (b) It can be seen that at 1623.34cm -1 The asymmetric stretching vibration of -COO-Na at 1645.71 cm -1 The vibration of -COO-Fe at 3432.52 cm indicates the formation of a strongly bound inner sphere complex between CMC and nano-ZVI. For fresh (unreacted in anoxic water) and aged (reacted in anoxic water for 14 days) CMC-nano-ZVI particles, the -OH stretching band increases from 3432.52 cm -1 Transfer to 3317.20cm -1 .CMC 400 -nZVI 10 The peak value of EPS has almost no change during the aging process. It can be inferred that aging has little effect on the interaction between CMC and nano-zero-valent iron. 10 -nZVI 10 FTIR spectrum ( Figure 6 (c) revealed the characteristic bands of pure EPS, such as the COC group of polysaccharide (1042 cm -1 ) and CN of quinone ring (1408cm -1 ). In addition, the interaction between EPS and nano-zero-valent iron was observed to cause a slowdown in the peak intensity of C=O. These changes reflect the strong interaction between iron ions or oxides and the corresponding functional groups in EPS, indicating that the coated EPS can weaken the Fe 0 Passivation. Figure 6 As can be seen in (d), the chemical functional groups of SDS are the binding sites for interaction with metal ions, at 2849.63, 2916.21 cm -1 The characteristic peak at 1085.38cm is due to the stretching vibration peak of the alkyl chain and CH of SDS. -1 and 1326.00cm -1The symmetric stretching vibration of S=O and the asymmetric stretching vibration of COS may be the key to the interaction mechanism between particles, indicating that SDS is successfully loaded on the surface of nano-zero-valent iron. SDS is adsorbed on the surface of nZVI through various interactions, thereby improving the anti-agglomeration performance of nanoparticles. Therefore, it is proved that the three modified materials are successfully coated on the surface of nano-zero-valent iron to form nano-zero-valent iron composite materials.
[0053] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for improving the anaerobic corrosion hydrogen evolution effect of nano zero-valent iron, characterized in that: The following steps are involved: (1) adding a polymer precursor solution into a reaction device, and introducing nitrogen gas to maintain an anaerobic environment in the reaction device; (2) uniformly dispersing the nano-zero-valent iron into the polymer precursor solution in step (1) to obtain a nano-zero-valent iron dispersion, stirring the dispersion under anaerobic conditions to obtain a nano-zero-valent iron composite material, and collecting the generated hydrogen using a gas collection bag; Wherein, the polymer precursor includes any one of sodium carboxymethyl cellulose, extracellular polymer and sodium dodecyl sulfate.
2. The method according to claim 1, characterized in that When the polymer precursor is sodium carboxymethyl cellulose, the concentration of the polymer precursor solution is 0.2-1.0 g / L; when the polymer precursor is extracellular polymer or sodium dodecyl sulfate, the concentration of the polymer precursor solution is 6-14 mg / L.
3. The method according to claim 1, characterized in that In the dispersion, the concentration of the nano zero-valent iron is 10 g / L.
4. The method according to claim 1, characterized in that: When the polymer precursor is sodium carboxymethyl cellulose, the concentration of the polymer precursor solution is 0.4 g / L.
5. The method according to claim 1, characterized in that When the polymer precursor is an extracellular polymer, the concentration of the polymer precursor solution is 10 mg / L.
6. The method according to claim 1, characterized in that When the polymer precursor is sodium dodecyl sulfate, the concentration of the polymer precursor solution is 12 mg / L.
7. The method according to claim 1, characterized in that In step (1), the step of adjusting the pH of the polymer precursor solution to 7.0±0.2 is also included.
8. The method according to claim 1, characterized in that The stirring includes mechanical stirring, the stirring speed is 200-400 rpm, and the stirring time is 30 minutes.
9. The nano zero-valent iron composite material prepared according to the method according to any one of claims 1 to 8.
10. Application of the nano zero-valent iron composite material according to claim 9 in the field of corrosion hydrogen evolution.